Web destekli bilgisayar öğretiminin tasarım kriterlerinin değerlendirilmesi - Arslan, Ahmet (My University, 2002)
WEB DESTEKLİ BİLGİSAYAR ÖĞRETİMİNİN TASARIM KRİTERLERİNİN DEĞERLENDİRİLMESİ Bu çalışmada web tabanlı eğitim-öğretim sunan sitelerin, tasarım kriterleri ışığında incelenmesi hedeflenmiştir. Bu bağlamda literatür bilgileri ışığında araştırıcılar tarafından belirlenen web tasarım kriterleri eşliğinde web tabanlı öğretim sunan eğitsel sitelerin sayfaları incelenmiştir. Bu sayfaların pencereleme teknikleri, ekran yoğunluğu, kullanışlılık gibi kriterleri ne derecede uyguladığı incelenmiştir. Her bir web sitesi, daha önceden hazırlanmış olan tasarım formu ile analiz edilmiştir. Formda yer alan her bir maddeye verilen matematiksel puan istatistiksel değer olarak yorumlanmıştır. Ayrıca öğretimsel web sitelerini kullananların beklentilerini belirlemek amacıyla oluşturulan Kullanıcı Beklentileri Değerlendirme Formu ile kullanıcıların öğretimsel web ortamlarından beklentileri belirlenmiş ve analiz edilen sitelerin bu beklentileri ne derecede karşıladığı ortaya konmuştur. Kısaca özetlersek analizini yaptığımız web sitelerinin büyük çoğunluğu ortanın üstüne çıkmayı başarmışlardır (4 puan) ancak kullanıcı beklentilerinin çok yüksek düzeylerde olmasından ötürü ilgili sitelerin büyük çoğunluğunun bu beklentileri karşılayabilecek seviyede olmadıkları görülmüştür. Formların bütün maddeleri için yaptığımız testlerde analiz formu ortalaması 4,72, kullanıcı beklentileri formu ortalaması 5,68'dir. Bir başka deyişle tasarım kriterlerinin %67'si incelediğimiz web ortamlarında bulunmakta ve kullanıcılar tasarım kriterlerinin %81'iyle yetinmektedirler. Ancak bu beklentilerini genel olarak şu anki web ortamlarından karşılama olanakları bulunmamaktadır.

This study is intended to examine the sites offering web-based education and instruction in the light of design criteria. Therefore, the pages of educational sites offering web-based instruction were examined using web design criteria determined by researchers in the light of literature information. To what extent these pages apply criteria such as windowing techniques, screen density and usability, was studied. Each website was analyzed with the design sheet prepared in advance. The mathematical score given to each article contained in the sheet was interpreted as a statistical value. In addition, with the User Expectations Evaluation Sheet, which was formed to determine the expectations of the users of the instructional websites, the expectations of the users from the instructional web media were determined and to what extent the analyzed sites met these expectations was put forth. Search engines were used in order to reach the sites offering computer instruction on the web. The fact that the quantity of such sites increase day by day and that they are updated with very short intervals, makes it difficult to determine the universe of the research. However, popular sites offering computer software and hardware instruction were reached by the help of search engines, and randomly selected 20 of these sites were determined as the study set of the reaserch. Also, the User Expectations Evaluation Sheet prepared in order to find out to what extent the web-based computer instruction met the user expectations was applied on a study set consisting of 103 individuals randomly selected from the undergraduate students of the Computer and Instruction Technologies Department, Atatürk Education Faculty, Marmara University, in the academic year 2001-2002. The Analysis Sheet (ANNEX-A), which was developed by the researchers in the light of literature information in order to determine whether the web-based computer instruction complies with the design criteria, and the User Expectations Evaluation Sheet (ANNEX-B), which was developed in the light of the literature information in order to find out to what extent the design criteria could meet the user expectations, were prepared in line with each other. That's especially in order to put forth clearly the stage of comparison of the user expectations and the compliance of the sites to the design criteria. The dependent variable articles in the relevant sheets are in line with each other and have the same number. The independent variable parts, however, do vary. The independent variables determined in the Analysis Sheet were the URL, Language, Browser Used and Loading Time, whereas those determined in the User Expectations Evaluation Sheet were Age, Gender, Class, Number of Browsers Being Used for the Web, Use of the Web for the Purpose of Learning in the Field of Computer, and the Number of Times the Web is Used per Week for the Purpose of Computer Learning. Frequency tables were prepared for the data obtained with the User Expectations Evaluation Sheet, which was prepared to determine the comments and preferences of the users with regard to design and find out to what extent the sites used meet them, and the percent values of the answers given for each article were found. In addition, One Way ANOVA was made to find out whether a significant difference existed among different classes according to the answers given to the questions, and an independent t-test was made to find out whether a difference existed between the two genders. The variance analyses and the independent t test were based on the significance level of .05. To summarize briefly, a great majority of the websites we have analyzed have managed to exceed the median (by 4 points), however, since the user expectations are very high, most of the relevant sites are found unable to meet these expectations. In the tests we have made for all articles of the sheets, the analysis sheet average is 4.72, and the user expectations sheet average is 5.68. In other words, 67% of the design criteria do exist in the web media we have examined, and the users are satisfied with 81% of the design criteria. In general, however, the current web media do not suffice to meet their expectations.
Keywords: Bilgisayar Destekli Eğitim; Web Siteleri_Tasarım